Immunostaining With Immunoglobulin G Subclass Antibody Cocktail for Diagnosis of Type 1 Autoimmune Pancreatitis. (December 2020) - Nakata, Rie; Uehara, Takeshi; Iwaya, Mai; Asaka, Shiho; Kobayashi, Shota; Sugano, Mitsutoshi; Higuchi, Kayoko; Kusama, Yukiko; Nakazawa, Koh; Nakaguro, Masato; Kobayashi, Mikiko; Tateishi, Ayako; et al.
Background: Immunoglobulin (Ig) G4-related diseases (RDs) are systemic diseases in which serum IgG4 levels are frequently elevated. They can cause diffuse or focal tumor formation, organ swelling, and tissue thickening in organs infiltrated by IgG4 + plasma cells. The diagnostic criteria for IgG4-RDs include an IgG4/IgG ratio >40%, but counting IgG + cells can be difficult because of the weakness of IgG staining density. We hypothesized that an antibody cocktail of mixed IgG1, IgG2, IgG3, and IgG4 (AC-IgG) might give immunohistochemistry results comparable with those of IgG in IgG4-RD. Methods: We compared AC-IgG reactivity with IgG expression in type 1 autoimmune pancreatitis (AIP), a representative IgG4-RD. We compared immunohistochemistry results using AC-IgG and IgG-only in 10 cases of AIP. The coefficient of variation (Cv) was used to analyze differences between AC-IgG and IgG findings in AIP by 13 board-certified pathologists. Results: Although mean values for IgG + cells did not significantly differ between AC-IgG (34.3; range = 27.4-37.1) and IgG (30.0; range = 23.0-45.6; P = .6254), Cv was lower for AC-IgG (33.4%) than for IgG (51.4%; regression equation; y [IgG] = 0.988 x + 0.982; correlation coefficient = 0.907). The data showed that the results of both methods were largely consistent. Conclusion: AC-IgG could replace IgG to count IgG + cells because of its lower Cv.